IDENTIFICATION OF PALM OIL PROCESSING AT PT. ASAM JAWA PKS - Febri Handika; Khairul Rizal; Yudi Triyanto; Hilwa Walida (RADJA PUBLIKA, 2025)
This study aims to determine the analysis of the palm oil processing identification process at PT. Asam Jawa in South Labuhanbatu Regency. The determination of the research location was done intentionally (purposive). The subjects of the study were the parties involved in the study, namely PT. Asam Jawa and the object of the study was the production of crude palm oil. Data collection was carried out using historical data methods and literature studies. The results of the study showed that the palm oil processing process starts from (a) fruit harvesting; (b) transportation of FFB; (c) receipt and sorting of FFB; (d) boiling station (Sterilizer); (e) threshing station; (f) pressing station; and (g) purification station (Clarification Station)